Sistem Monitoring Konsumsi Daya Listrik Berbasis IoT untuk Efisiensi Energi pada Gedung PENMARU Universitas Muhammadiyah Lampung - Yudi Eka Putra; Oktavia Eka Rahayu; Yenni Afrida; Jeckson Jeckson; Fitriono Fitriono; Sri Suryani (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2026)
Abstract. Electrical energy usage in buildings with three-phase distribution systems requires proper monitoring to ensure energy consumption can be controlled effectively and efficiently. Common problems in building electrical systems include load imbalance between phases, delayed fault detection, and manual monitoring processes that prevent real-time observation of power consumption conditions. This study aims to design and develop an Internet of Things (IoT)-based electrical power consumption monitoring system for the PENMARU Building of Muhammadiyah University of Lampung using the PZEM-004T sensor and ESP32 microcontroller. The system was designed to monitor electrical parameters such as voltage, current, active power, electrical energy, and power factor in a three-phase electrical system in real-time through an IoT-based monitoring dashboard. The research method used in this study was Research and Development (R&D), which included system design, hardware and software implementation, system testing, and analysis of measurement results. The results showed that the system was able to monitor electrical parameters in real-time with a measurement error below 1%. The seven-day testing results indicated that the average power on phase R was 74.86 W, phase S was 225.64 W, and phase T was 51.01 W, with total electrical energy consumption reaching 47.06 kWh. In addition, the system successfully transmitted monitoring data stably through a Wi-Fi network and displayed the data on the IoT dashboard in real-time. Therefore, the proposed monitoring system is considered capable of supporting more effective, responsive, and efficient electrical energy consumption monitoring.